Reduce the Incidence of Flour Albus Using the Betel Leaves Extract - Risman Tunny; Aulia Deby Pelu; Jarmil Soulissa (Alliance of Health Activists (AloHA), 2021)
Vaginal discharge is often not taken seriously by the teens when it could be an indication of disease. Vaginal discharge is a second problem after menstrual disorders. It is very uncomfortable, itchy, smelly and sometimes sore. Betel leaves boiled water to wash the vagina can reduce vaginal discharge because it contains essential oils that consist of betlephenol, kavicol, sidquiterpan, hydroxycicvicol, cavibetol, estragol, eugenol, and carvacol. The objective of this research is to describe the effect of betel leaves extract on the occurrence of flour albus on teenagers of SMA 3 west Seram western Seram regency 2015. It is a quantitative research by using quasy-experiment design to determine the existence of vaginal discharge (pre-test) and examine the effectiveness of the betel leaves extract after treatment (post-test). The sample were 18 respondents with observation sheet given. Research result shows that 13 of 18 respondents who experienced vaginal discharge cured after being treated in the form of betel leaves extract. It can be concluded that vaginal discharge before and after the treatment is given for the provision of betel leaves extract is different or experience the healing significantly. Keywords: betel leaves extract; vaginal discharge